1998
DOI: 10.1046/j.1365-2788.1998.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Community care for adults with Williams syndrome: how families cope and the availability of support networks

Abstract: A study of the adjustment difficulties and needs of 70 adults with Williams syndrome found that the majority continued to live at home and remained heavily dependent on their families for their self-care. Twenty-nine families (41.4%) had had no contact with a social worker in the preceding 2 years, and 34 out of the 48 families whose children still lived at home (70.8%) had no access to respite care. Advice regarding benefits, and appropriate living and occupational arrangements for the adults was also patchy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
3
23
0
1
Order By: Relevance
“…1994; Mervis et al. 2001), and adults have particular difficulty coping with the demands of employment (Udwin et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…1994; Mervis et al. 2001), and adults have particular difficulty coping with the demands of employment (Udwin et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Estas três famílias participaram num estudo piloto cujo objectivo era examinar a situação psicossocial de famílias portuguesas e alemãs com um membro com o síndrome de Williams. O ponto de partida relacionava-se com questões como: Com que exigências, expectativas e dificuldades têm os membros da família (incluindo o afectado pelo síndrome) de se confrontar, como lidam eles com estes problemas no quotidiano e que ajudas é que necessitam (Udwin et al, 1998)? A ter em linha de conta estavam as suas necessidades e questões, assim como os comportamentos íntimos à família, relações afectivas e reacções de cada um dos membros.…”
Section: Introductionunclassified
“…Self-regulation has been associated with the neurobiological substrates of the OFC, the dorsolateral prefrontal cortex, and the anterior cingulate cortex (Whittle et al, 2006). Difficulties with self-regulation, such as poor inhibition, poor adaptability, perseveration, and hyperactivity, have been documented as weaknesses for individuals with WS (Arnold et al, 1985;Davies et al, 1998;Dilts et al, 1990;Dykens & Rosner, 1999;Gosch & Pankau, 1994;Klein-Tasman & Mervis, 2003;Tomc et al, 1990;Udwin, 1990;Udwin et al, 1998;Udwin & Yule, 1991;Udwin, Yule, & Martin, 1987). Further, executive functioning abilities have been associated with anxiety, problem behaviors, and sensory modulation difficulties in children with WS, underscoring the significance of these regulatory skills (John & Mervis, 2010 Gioia et al, 2000) to investigate the association between aspects of executive functioning and the probability of having an anxiety disorder in children with WS.…”
Section: Anxiety In Individuals With Williams Syndromementioning
confidence: 99%
“…Specifically, studies have shown that individuals with WS have difficulty with inhibitory control as indexed by measures of hyperactivity, approach, and attention seeking behaviors (Arnold et al, 1985;Dilts et al, 1990;Dykens & Rosner, 1999;Klein-Tasman & Mervis, 2003;Tomc et al, 1990;Udwin, 1990;Udwin et al, 1998;Udwin & Yule, 1991). Individuals with WS also have been shown to demonstrate difficulties with set-shifting and emotion regulation, as indexed by measures of low adaptability, high preoccupations, low persistence, high levels of stress reaction, and increased temper tantrums Klein-Tasman & Mervis, 2003;Tomc et al, 1990;Udwin, 1990;Udwin et al, 1987).…”
Section: Anxiety In Individuals With Williams Syndromementioning
confidence: 99%
See 1 more Smart Citation